EVOLUTION OF THE CONCEPT OF NATIONAL MINORITIES IN UKRAINE - Borodin, Ivan; Vodolaskova, Kateryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the study is a scientific analysis of the conceptual apparatus in the context of the stated issues, to clarify issues related to the legislation on the legal personality of national minorities, to determine the main prospects in this area. Research methods: the methodological basis of the work is a comprehensive approach to the analysis of the conceptual foundations of national minorities. It is based on the dialectical method of research, as well as the method of analytical, comparison, and hysteria, which provide identification of the inner essence of phenomena through the characteristics of the dynamics of their development and external manifestations. Results: the relevance of the study of the rights of national minorities is related to the need to create a theoretical basis for legal status and protection of their rights, with the need to improve existing legislation in this area in accordance with current trends in international law. The development of the protection of the rights of national minorities is primarily connected with European states. Today there is a fairly clear and effective system of protection of the rights of national minorities under international law. But there are also unresolved issues in the system of protection of the rights of national minorities under international law. However, the development of protection of the rights of national minorities by the norms of international law is gradually overcoming obstacles to the establishment of a system of protection of the rights of national minorities.The evolution of the concept of a national minority indicates the prospects for further development of their legal personality. Discussion: in addition to the scientific value, as well as the possibilities of application in the educational process of this article should be pointed out its relevance to the legislative and legislative process. The practical significance of the article is that it provides an opportunity to focus legal doctrine on the needs of practice.